Effect of four species of arbuscular mycorrhizal fungi on the production of tomato fruits - Ley-Rivas, Juan Francisco (2015)
The effect of native arbuscular mycorrhizal fungi (AMF) Glomus sp. 1, Glomus sp. 2, Glomus clarum and Glomus intraradices on tomato (Solanum lycopersicum L. Var., amalia) was evaluated under controlled conditions by means of growth variables (height, stem diameter, number of leaves, flowers and fruits, dry aerial and underground biomass and fresh mass of fruits) and the mycorrhizal variables (colonization, visual density, quantification of endophyte, external mycelium and spores). The strains Glomus sp. 1 and Glomus intraradices were the most efficient, with harvest index values of 65 and 56.3% and fruit fresh weight of 166.7 and 131.8 g, respectively. It is emphasized that the fungal strain Glomus sp. 1 always presented lower values than strain Glomus intraradices.